Aplikasi Inventori Barang Berbasis Web Menggunakan PHP Pada M Mart: Web Based Goods Inventory Application Using PHP at M Mart - Wahyu Akbar; Julius Panda Putra Naibaho; Marlinda Sanglise (JISTECH: Journal of Information Science and Technology, 2024)
The development of technology in this world is very rapid and has spread to various aspects of life. Technology also makes it very easy for us to make our work easier, one of which is managing stock at a place of business. M Mart is a business place or place to shop for daily necessities, food and drinks, as well as equipment commonly used for household needs, which still uses manual methods for managing and storing stock, incoming goods, outgoing goods. This is felt to be less effective and inefficient, because in the process of processing and storing data on stock of goods, incoming goods, outgoing goods, this will result in ineffectiveness in data processing and storage. To overcome this problem, the company needs a form of information system, namely a web-based inventory application that can help in carrying out the work of work units in managing and storing data, especially regarding stock of goods, incoming goods, outgoing goods.